Leading Technological Change - Case Study of Emirates Airlines - Al-Nakeeb, Ahmed; Darwish, Hessa; Alhajri, Reem (International Journal of Technology and Systems, 2023)
Purpose: Emirates Airlines is one of the leading airlines with over 100 international destinations. The airline sector is continually evolving, bringing both difficulties and possibilities. Emirates Airlines has reacted to these changes by effecting an organizational change plan. Implementing a Resource Management System (RMS) in the line maintenance department is the primary subject of this study since it was the main change in the Emirates. Based on specified criteria and flight updates, the RMS software program produces jobs for technicians and engineers. Therefore the study aims to evaluate how the organization handles the change process after introducing new technological applications in the emirates airlines. Methodology: This study employs various qualitative research techniques, including interviews. Findings: The study reveals that critical leadership traits for implementing change include self-awareness, self-regulation, empathy, self-motivation, and social skills. Embracing change enables organizations to enhance their services and provide a distinct competitive edge compared to resistance, which can render the firm irrelevant. Resistance to change mainly occurs due to inadequate information, poor comprehension, and varying visions (Elgohary & Abdelazyz, 2020). Unique Contribution to Theory, Practice and Policy: The study was anchored on change model. The study recommends that the RMS should benefits the department by improving labor utilization, lowering maintenance costs, and raising customer satisfaction.